Electrodeposited nickel–graphene nanocomposite coating: effect of graphene nanoplatelet size on its microstructure and hardness. Issue 37 (9th June 2020) - Van Hau, Tran; Van Trinh, Pham; Hoai Nam, Nguyen Phuong; Van Tu, Nguyen; Lam, Vu Dinh; Phuong, Doan Dinh; Minh, Phan Ngoc; Thang, Bui Hung
Abstract : The effect of graphene nanoplatelet size on the microstructure and hardness of electrodeposited nickel–graphene nanocomposite coatings was investigated. Abstract : In this study, the effect of graphene nanoplatelet (GNP) size on the microstructure and hardness of the electrodeposited nickel–graphene nanocomposite coatings were investigated. GNPs with different sizes were prepared by using a high energy ball milling technique. The experimental result revealed the high energy ball milling technique could reduce the size, increase the surface area, and improve the dispersion ability of GNPs. The microstructure, hardness, and components of the nanocomposite coatings were greatly affected by GNP sizes. The highest microhardness was measured to be 273 HV for the nanocomposite coatings containing 5 h-milled GNPs, which is increased up to ∼47% compared to pristine Ni coating. The enhancement in the hardness is attributed to the uniform dispersion of the small GNP sizes inside the Ni matrix and the Ni grain size reduction when using milled GNPs.